2017
DOI: 10.1016/j.imr.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Study on pharmacokinetics and tissue distribution of single dose oral tryptanthrin in Kunming mice by validated reversed-phase high-performance liquid chromatography with ultraviolet detection

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 19 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…[20][21][22][23] Even in animal models, multiple biopsies of tumors are technically challenging, and so researchers typically carry out PK studies by collecting samples from multiple animals sacrificed at different time-points, producing averaged population data that do not accurately capture intra-tumor variability from individual animals. 24 Furthermore, these experiments are being performed ex vivo, and may not accurately capture the physiological behavior of a tumor within its in vivo milieu. More generally, such analyses are challenging to perform for a variety of reasons-for instance, the probe needs to withstand insertion into solid tissue with minimal sensor damage, and must be sufficiently resistant to biofouling to enable robust measurement over extended periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23] Even in animal models, multiple biopsies of tumors are technically challenging, and so researchers typically carry out PK studies by collecting samples from multiple animals sacrificed at different time-points, producing averaged population data that do not accurately capture intra-tumor variability from individual animals. 24 Furthermore, these experiments are being performed ex vivo, and may not accurately capture the physiological behavior of a tumor within its in vivo milieu. More generally, such analyses are challenging to perform for a variety of reasons-for instance, the probe needs to withstand insertion into solid tissue with minimal sensor damage, and must be sufficiently resistant to biofouling to enable robust measurement over extended periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…Eighty Kunming mice40 were randomly divided into three groups: 30 mice in the control group, 45 mice in the experimental group, and 5 mice in the blank group. All of the mice were fasted for 12 hrs before experiments, with free access to water.…”
Section: Characterizationmentioning
confidence: 99%
“… 46 , 47 In contrast, a number of metabolites such as tryptanthrin play a renoprotective role. 48 Notably, tryptophan can be transformed into two beneficial metabolites by TPH, and our recent studies indicated the two metabolites, 5-MTP and melatonin, exhibited a renoprotective role in CKD. 10 , 11 , 16 Both TPH-1 and TPH-2 convert tryptophan to 5-hydroxytryptophan (5-HTP).…”
Section: Discussionmentioning
confidence: 99%